Association of sepsis-induced cardiomyopathy and mortality: a systematic review and meta-analysis - Yu-Min Lin; Mei-Chuan Lee; Han Siong Toh; Wei-Ting Chang; Sih-Yao Chen; Fang-Hsiu Kuo; Hsin-Ju Tang; Yi-Ming Hua; Dongmei Wei; Jesus Melgarejo; Zhen-Yu Zhang; Chia-Te Liao (Annals of Intensive Care, 2022)
Abstract Background The implication of sepsis-induced cardiomyopathy (SIC) to prognosis is controversial, and its association with mortality at different stages remains unclear. We conducted a systematic review and meta-analysis to understand the association between SIC and mortality in septic patients. Methods We searched and appraised observational studies regarding the mortality related to SIC among septic patients in PubMed and Embase from inception until 8 July 2021. Outcomes comprised in-hospital and 1-month mortality. We adopted the random-effects model to examine the mortality risk ratio in patients with and without SIC. Meta-regression, subgroup, and sensitivity analyses were applied to examine the outcome’s heterogeneity. Results Our results, including 20 studies and 4,410 septic patients, demonstrated that SIC was non-statistically associated with increased in-hospital mortality, compared to non-SIC (RR 1.28, [0.96–1.71]; p = 0.09), but the association was statistically significant in patients with the hospital stay lengths longer than 10 days (RR 1.40, [1.02–1.93]; p = 0.04). Besides, SIC was significantly associated with a higher risk of 1-month mortality (RR 1.47, [1.17–1.86]; p < 0.01). Among SIC patients, right ventricular dysfunction was significantly associated with increased 1-month mortality (RR 1.72, [1.27–2.34]; p < 0.01), while left ventricular dysfunction was not (RR 1.33, [0.87–2.02]; p = 0.18). Conclusions With higher in-hospital mortality in those hospitalized longer than 10 days and 1-month mortality, our findings imply that SIC might continue influencing the host’s system even after recovery from cardiomyopathy. Besides, right ventricular dysfunction might play a crucial role in SIC-related mortality, and timely biventricular assessment is vital in managing septic patients.